80‐1: An Integral Imaging Display Based on a Micro Liquid Lens Array. Issue 1 (May 2016) - Zhao, Wu-Xiang; Dong, Yan-Yu; Deng, Huan; Wang, Qiong-Hua
Abstract : An integral imaging (II) 3D display based on a micro liquid lens array (MLLA) is presented. The II 3D display is composed of a MLLA proposed by us and 2D display panel. An II display prototype based on the MLLA is developed and realizes II 3D display and 2D display